The global multidimensional poverty index (MPI) 2020 - Sabina Alkire; Kanagaratnam, U; Suppa, N (Oxford Poverty and Human Development Initiative (OPHI), 2020)
This document presents the methodology and technical decisions behind the global Multidimensional Poverty Index (MPI) 2020, the Stata do-files, and the results presented in Tables 1–5. This document is part of OPHI’s Methodological Notes series. A Methodological Note is published for every release of the global MPI.